En route to dynamic life processes by SNARE-mediated fusion of polymer and hybrid membranes - Lado Otrin (Nature Portfolio, 2021)
A variety of artificial cells springs from the functionalization of liposomes with proteins but these models suffer from low durability without repair and replenishment mechanisms. Here, the authors show that synthetic amphiphile membranes undergo SNARE-mediated fusion, and determine bending rigidity and pore edge tension as key parameters for fusion.